Encyclopedia of Hydrological Sciences 2005
DOI: 10.1002/0470848944.hsa007
|View full text |Cite
|
Sign up to set email alerts
|

Fractals and Similarity Approaches in Hydrology

Abstract: The application of fractals and similarity concepts in hydrology has given rise to a better understanding of the space‐time organization of forms and processes that are relevant to the hydrologic cycle. Indeed, a variety of literature results support the conjecture that scaling holds for most hydrological variables in time and space. This chapter concentrates on fields where fractals and similarity approaches have proved helpful in fostering advances in specific hydrological studies. In particular, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Since the excess rainfall rate i ( x , t ) is assumed to be a known self‐similar function for the example problem, one can obtain one more condition on the scaling exponents from the self‐similar functional form of this dependent variable. In this study, the functional form of i ( x , t ) is set to ‘power‐law’ form due to its well‐known self‐similar property (Lanza and Gallant, 2006). Let i ( x , t ) = I 0 · t a · x b , where I 0 , a and b are known real numbers.…”
Section: The Scale Invariance Of the Kinematic Wave Overland Flow Promentioning
confidence: 99%
“…Since the excess rainfall rate i ( x , t ) is assumed to be a known self‐similar function for the example problem, one can obtain one more condition on the scaling exponents from the self‐similar functional form of this dependent variable. In this study, the functional form of i ( x , t ) is set to ‘power‐law’ form due to its well‐known self‐similar property (Lanza and Gallant, 2006). Let i ( x , t ) = I 0 · t a · x b , where I 0 , a and b are known real numbers.…”
Section: The Scale Invariance Of the Kinematic Wave Overland Flow Promentioning
confidence: 99%
“…Due to the application of the previous methods, it has been found that rainfall possesses fractal properties (Venugopal et al 1999;Amaro et al 2004;Beran 1994;Oñate 1997;Peters et al 2002;Schertzer et al 2010;Turcotte 1994;Lanza and Gallant 2006;Hubert and Carbonnel 1990); however the distribution of rainfall drops do not have these properties (Malinowki et al 1993;Lovejoy and Schertzer 1987Hentschel and Procaccia 1984;Lombardo et al 2012). …”
Section: Introductionmentioning
confidence: 99%